Isolation and X-ray characterization of palladium–N complexes in the guanylation of aromatic amines. Mechanistic implications - Grirrane, Abdessamad; Garcia, Hermenegildo; Álvarez, Eleuterio (Beilstein Journal of Organic Chemistry, 2013)
In the context of palladium-catalyzed guanylation of anilines herein, we have been able to characterize and isolate bis(anilino) and bis(guanidino)Pd(II) complexes using reaction conditions under which stoichiometric amounts of palladium salts are used. Characterization of these palladium complexes strongly supports a mechanistic proposal for the catalytic guanylation of anilines using PdCl2(NCCH3)2 as catalyst that involves the intermediacy of these Pd(II) complexes.
Keywords: coordination chemistry; guanylation reaction; homogeneous catalysis; palladium complexes; reactive intermediates